Enhancing Students’ Independence of Learning: Problem-Based Learning Model Integrated with TaRL and CRT Strategies - Santoso, Evi Zulfiani (International Journal of Research in Mathematics Education, 2024)
The results of observations that have been made in class X E9 SMA Negeri 5 Purwokerto show that the problem that exists in Mathematics learning is the lack of student independence, many students do not carry out independent evaluations individually and according to their abilities. There are still students who lack awareness in preparing themselves before the learning process begins. This can be seen when the teacher starts learning activities, only a small number of students prepare themselves before the learning process begins. When students are given an assignment, they don't do it straight away but still depend on their friends, for example, if they are given practice questions, they still look at their friends' answers. Seeing this, learning is needed that actively involves students and can make students dare to try to use their own abilities in solving problems. Therefore, the author is interested in this research. Learning with the Problem Based Learning model accompanied by TaRL and CRT approaches in Probability material in class X E9 SMA Negeri 5 Purwokerto can increase the percentage of students' learning independence from cycle I to cycle III by 39.6%.